Employees’ Commitment – Psychological and Organizational Aspects (Economic and Political Thought, 2013)
The issue of the organizational commitment and management by commitmentbelongs to the current and extremely utilitarian issues considered on thebasis of management theory and practice. The article has an epistemologicalcharacter. Its aim is to systematize the knowledge of the commitment issueand formulate, on this ground, issues for further scientific research.